MOTIF PENANAMAN RELIGIOUS CULTURE DI SMPN 3 TUBAN - Hidayah, Nurul (Paradigma, 2021)
Religious culture is an act of habituation that has religious values. The cultivation of religious culture in schools has a role in shaping the character of students. In general, religious activities occur in schools with the status of religious schools. However, one of the schools in Tuban is SMPN 3 Tuban, which is a public and state school that pays special attention and has its own characteristics in inculcating religious culture. This study aims to uncover the motives for planting religious culture at SMPN 3 Tuban. This study uses qualitative research methods with phenomenological analysis from the perspective of Alfred Schutz. The data collection of this research was carried out using observation, interviews and documentation. Based on the phenomenological perspective of Alfred Schutz in this study, it shows because of the motive (causal motive) and the sequence of motives (destination motive). Because the motive for cultivating religious culture is that the condition of the school is still minimal from religious values. Starting from these conditions, one of the teachers was moved to make changes by fostering a religious culture. The motive of the goal is to improve the practice of religious teachings, improve reading and understanding of the Qur’an and the Bible, as well as good morals. Keywords: motive, cultivation, and religious culture.